Municipal Development Initiatives in Cuba (Revista LIDER, 2020)
In Cuba, the municipal and regional development stems in large disparities and socioeconomic inequalities pre triumph of the Revolution of January 1959, and therefore of the need to invest efforts towards the ordering of the territories for development in relation to the revolutionary process. This study concerns the institutional framework of municipal development in Cuba and the effects of municipal development initiatives in other areas of participation and local development, with cases exemplifying.